Uterus didelphys with obstructed hemivagina with chronic presentation: a case report - Anant, Monika; Das, Bibekanand; Bhadra, Avishek; Mukherji, Joydev (International Journal of Research in Medical Sciences, 2017)
This is a case report of a 24-year patient who had uterus didelphys with obstructed hemivagina. Clinical manifestations of this case were of progressive dysmenorrhea, abdominal pain after menarche, cyclic difficulty in urination and constipation, with the existing paravaginal tumor indicated this rare anomaly. The diagnosis was by clinical examination and ultrasonography. The patient underwent successful transvaginal septoplasty and drainage of the hematocolpos and hematometra, which is the appropriate mode of treatment in such cases.